Virtual Reality Assessment of Classroom – Related Attention: An Ecologically Relevant Approach to Evaluating the Effectiveness of Working Memory Training - Coleman, Benjamin; Marion, Sarah; Rizzo, Albert; Turnbull, Janiece; Nolty, Anne (Frontiers in Psychology, 2019)
Computerized cognitive interventions to improve working memory also purport to improve ADHD-related inattention and off task behavior. Such interventions have been shown to improve working memory, executive functioning, and fluid reasoning on standardized neuropsychological measures. However, debate continues as to whether such programs lead to improvement on ecologically relevant outcomes, such as classroom behavior. This study sought to propose a novel, ecologically relevant approach to evaluate the effectiveness of working memory training on real-world attention performance. Participants included 15 children, aged 6–15, identified as having attention problems were assessed via the virtual classroom continuous performance task (VCCPT) before and after completing 5 weeks of Cogmed working memory training. The VCCPT is a validated measure of sustained and selective attention set within a virtual reality (VR) environment. Several key areas of attention performance were observed to improve, including omission errors, reaction time, reaction time variability, and hit variability. Results suggest that working memory training led to substantial improvements in sustained attention in a real-life scenario of classroom learning. Moreover, the use of psychometrically validated VR measurement provides incremental validity beyond that of teacher or parent report of behavior. Observing such improvements on ecologically relevant measures of attention adds to the discussion around how to evaluate the effectiveness of working memory training as it pertains to real-life improvements and serves to inform consumer awareness of such products and their claims.